1998
DOI: 10.1046/j.1523-1755.1998.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential upregulation of rat Na-K-Cl cotransporter, rBSC1, mRNA in the thick ascending limb of Henle in different pathological conditions

Abstract: rBSC1 is differentially upregulated in different pathological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 19 publications
4
42
0
Order By: Relevance
“…63,64 In addition, studies in rats with mild heart failure have found increased expression of the Na-K-2Cl cotransport in the thick ascending limb of Henle's loop, a phenomenon associated with not only augmented sodium but also water reabsorption capacity. 65,66 As we indicated previously, 9 it is unlikely that exact mechanisms and gene variants causing the sodium-sensitive type hypertension in laboratory animals are also responsible for sodium sensitivity in blacks, but the physiological principles that govern renal sodium and water homeostasis are shared by all mammals. Thus, these animal models support the thesis that an increase in the activity of Na-K-2Cl cotransport in the thick ascending limb of Henle's loop augments not only sodium but also water reabsorption.…”
Section: Further Clues For Sodium Sensitivity In Blacks Based On Potamentioning
confidence: 89%
“…63,64 In addition, studies in rats with mild heart failure have found increased expression of the Na-K-2Cl cotransport in the thick ascending limb of Henle's loop, a phenomenon associated with not only augmented sodium but also water reabsorption capacity. 65,66 As we indicated previously, 9 it is unlikely that exact mechanisms and gene variants causing the sodium-sensitive type hypertension in laboratory animals are also responsible for sodium sensitivity in blacks, but the physiological principles that govern renal sodium and water homeostasis are shared by all mammals. Thus, these animal models support the thesis that an increase in the activity of Na-K-2Cl cotransport in the thick ascending limb of Henle's loop augments not only sodium but also water reabsorption.…”
Section: Further Clues For Sodium Sensitivity In Blacks Based On Potamentioning
confidence: 89%
“…In support of this concept, recent studies demonstrate that enhanced expression of BSC-1 in the TAL causes sodium retention in rats with congestive heart failure. 3 Moreover, BSC-1 is upregulated in rats with small-to-moderate myocardial infarctions, 4 dehydration, and cardiac failure 5 and in an animal model of liver cirrhosis. 6 Moreover, our results in the spontaneously hypertensive rat (SHR) show that expression of BSC-1 is also elevated in this animal model of essential hypertension and that the natriuretic response to furosemide (which blocks BSC-1) is significantly higher in the SHR compared with its normotensive counterpart, suggesting that BSC-1 could be involved in the development and/or maintenance of hypertension in the SHR.…”
mentioning
confidence: 99%
“…Moreover, BSC-1 is up-regulated in rats with small to moderate myocardial infarctions (Nogae et al, 2000), dehydration, and cardiac failure (Marumo et al, 1998). Finally, mutations in the NKCC2 gene, which encodes BSC-1 presumably by inducing a loss of function of the transporter, result in Bartter's syndrome, an inherited disease characterized by hypokalemic metabolic alkalosis, hypercalciuria, salt wasting, and volume depletion resulting in hypotension (Simon et al, 1996;Vargas-Poussou et al, 1998).…”
mentioning
confidence: 99%